2017
DOI: 10.1007/s00787-017-1003-1
|View full text |Cite
|
Sign up to set email alerts
|

Predicting academic impairment and internalizing psychopathology using a multidimensional framework of Sluggish Cognitive Tempo with parent- and adolescent reports

Abstract: Adolescents with Sluggish Cognitive Tempo (SCT) exhibit symptoms of slowness, mental confusion, excessive daydreaming, low motivation, and drowsiness/sleepiness. Although many symptoms of SCT reflect internalizing states, no study has evaluated the clinical utility of self-report of SCT in an attention-deficit/hyperactivity disorder (ADHD) sample. Furthermore, it remains unclear whether SCT is best conceptualized as a unidimensional or multidimensional construct. In a sample of 262 adolescents comprehensively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 32 publications
6
34
0
Order By: Relevance
“…Toward this end, although a standard symptom set for assessing SCT is itself an important goal, it may be easier for investigators to freely examine its measurement -both at the construct level and at the individual symptom level. There may also be separate dimensions within SCT that are important to examine in terms of etiology, course, and associations with impairment and treatment response [27,40,[100][101][102][103][104]. In agreement with Lahey and colleagues [23], the overarching SCT construct may be too large a "grain size" for understanding its psychobiology since it includes a range of cognitive, psychomotor, and motivational components while at the same time the SCT construct may be too small if not examined and understood within higher-order models of psychopathology.…”
Section: Key Considerations For Examining Sct Within Hierarchical Modmentioning
confidence: 99%
“…Toward this end, although a standard symptom set for assessing SCT is itself an important goal, it may be easier for investigators to freely examine its measurement -both at the construct level and at the individual symptom level. There may also be separate dimensions within SCT that are important to examine in terms of etiology, course, and associations with impairment and treatment response [27,40,[100][101][102][103][104]. In agreement with Lahey and colleagues [23], the overarching SCT construct may be too large a "grain size" for understanding its psychobiology since it includes a range of cognitive, psychomotor, and motivational components while at the same time the SCT construct may be too small if not examined and understood within higher-order models of psychopathology.…”
Section: Key Considerations For Examining Sct Within Hierarchical Modmentioning
confidence: 99%
“…There is less clear evidence linking SCT to academic functioning. Some recent studies have found SCT symptoms to be associated with greater academic impairment ratings, above and beyond ADHD-IN symptoms (Khadka, Burns, & Becker, 2016;Lee, Burns, Beauchaine, & Becker, 2016;Smith & Langberg, 2017), though mixed findings have also been reported (Belmar, Servera, Becker, & Burns, 2017;Lee, Burns, & Becker, 2018). The evidence is also mixed among studies examining SCT in relation to academic achievement test performance.…”
Section: Introductionmentioning
confidence: 99%
“…Caregiver reports of SCT symptoms have been linked to overall reports of academic impairment, with a generally moderate effect size (Becker et al, 2016). Specifically, SCT is associated with reported academic impairment ratings from parents or teachers (Bauermeister, Barkley, Bauermeister, Martinez, & McBumett, 2012; Jacobson et al, 2012; Langberg, Becker, & Dvorsky, 2014; Smith & Langberg, 2017; Watabe, Owens, Evans, & Brandt, 2014), with associations inconsistently remaining after controlling for inattention and/or intellectual ability/IQ. Nevertheless, existing evidence is inconsistent, with some work suggesting that SCT ratings are not associated with reported academic impairment beyond ADHD symptoms (e.g., Becker & Langberg, 2013; Carlson & Mann, 2002; Marshall, Evans, Eiraldi, Becker, & Power, 2014) or that only some but not all SCT dimensions show association with reported academic impairment (e.g., Slow SCT; Tamm et al, 2016) or grade point average (e.g., SCT Slow factor associated with reduced grades, while the Daydreamy factor was associated with higher grades; Smith & Langberg, 2017).…”
mentioning
confidence: 98%